2021
DOI: 10.1140/epje/s10189-021-00033-w
|View full text |Cite
|
Sign up to set email alerts
|

Active colloids under geometrical constraints in viscoelastic media

Abstract: We study the behavior of active particles (APs) moving in a viscoelastic fluid in the presence of geometrical confinements. Upon approaching a flat wall, we find that APs slow down due to compression of the enclosed viscoelastic fluid. In addition, they receive a viscoelastic torque leading to sudden orientational changes and departure from walls. Based on these observations, we develop a numerical model which can also be applied to other geometries and yields good agreement with experimental data. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Note also that most of the experimental and theoretical studies with active colloids focus on the behavior in purely viscous Newtonian fluids, whereas the natural environment for many active particles such as bacteria and cells are non-Newtonian viscoelastic fluids [313,314]. Recent exceptions include the experimental works [315][316][317] which have provided important insights into the dynamics of active particles in viscoelastic media (so far mainly at the single particle level). In addition, the very recent theoretical work [318] has shown that viscoelastic effects can significantly modify the slip velocity on the active surface of the particles, which should have profound consequences not only for the single particle behavior but also for the (phoretic) cross-interactions of these particles.…”
Section: Memory and Solute Advection Effectsmentioning
confidence: 99%
“…Note also that most of the experimental and theoretical studies with active colloids focus on the behavior in purely viscous Newtonian fluids, whereas the natural environment for many active particles such as bacteria and cells are non-Newtonian viscoelastic fluids [313,314]. Recent exceptions include the experimental works [315][316][317] which have provided important insights into the dynamics of active particles in viscoelastic media (so far mainly at the single particle level). In addition, the very recent theoretical work [318] has shown that viscoelastic effects can significantly modify the slip velocity on the active surface of the particles, which should have profound consequences not only for the single particle behavior but also for the (phoretic) cross-interactions of these particles.…”
Section: Memory and Solute Advection Effectsmentioning
confidence: 99%
“…23 In addition, the JCs are also known to slow down upon reaching close to a solid boundary due to the resultant viscoelastic stresses that arise when the fluid between the JC and the boundary is compressed. 52 Despite all these noteworthy experimental observations reported on light-activated JCs, only Saad and Natale have attempted to experimentally explore the behavior of the selfdiffusiophoretic motion of SiO 2 −Pt active Janus colloids in a few dilute and semidilute polymer solutions. The study concluded that the polymeric entanglements physically confine the JCs and restrict their motion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many of the various types of self-propelled objects that have been analyzed over the past decades feature an intrinsic polar direction setting their direction of motion. Examples are the famous biological microswimmers Escherichia coli 1,2 or Chlamydomonas reinhardtii 3 , animals like birds 4 or fish 5,6 , synthetic microswimmers in the form of Janus colloidal particles 7,8 , or vibrated polar hoppers 9,10 . Various works have addressed the displacement statistics of such self-propelled or actively driven objects [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%